BIRTHING BALL THERAPY INTERVENTION WITH PELVIC ROCKING TECHNIQUE IN REDUCING THE INTENSITY OF BACK PAIN IN PREGNANT WOMEN IN THE THIRD TRIMESTER AT THE KLAMBU HEALTH CENTER - Ucik Rosyidah; Dhiyan nany Wigati; Nurul Kodiyah (The Shine Cahaya Dunia Kebidanan, 2024)
Background: Pregnancy lasts 280 days (40 weeks) and is divided into three quarters and three trimesters. Physical and physiological changes during pregnancy can cause discomfort such as back pain. Non-pharmacological techniques such as birth ball can help reduce such pain. The purpose of this research is to be able to carry out Midwifery Care with the focus of intervention Birthing Ball Treatment through Pelvic Rocking Relaxation Technique to Minimize Back Pain Intensity in Pregnant Women in the Third Trimester at Klambu Health Center. Methodology: This research methodology uses a descriptive case study design with a participatory observation approach to assess midwifery care for pregnant women who experience back discomfort in the third trimester. The study was conducted at the Klambu Community Health Center with the subject of pregnant women aged 21-35 years without high risk. Data were collected using assessment sheets, implementation strategies, and documentation. Data collection methods include research permits, approval of health centers, evaluation of birthing ball therapy interventions with pelvic rocking techniques for 7 days with a frequency of 1x/day for 30-45 minutes in 3 movements, with the duration of each movement 10-15 minutes.  Results: The study results indicate a significant reduction in back pain for Mrs. L, with a pain scale score decreasing from 6 before the intervention to 3 after the intervention. This reduction shows that the birth ball intervention was effective in decreasing pain intensity, with the patient reporting that the pain was now manageable and did not interfere with daily activities. Conclusion: Based on the case report, after intervention with birthing ball therapy using the pelvic rocking technique for 7 days, it successfully in reduced Mrs. L's back pain from a pain scale of 6 to pain scale of 3.